Integrating Traditional and Modern Approaches to Develop Creativity in Fine Arts Education - Ismoilov Otabek Shavkat o‘g‘li (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores the integration of traditional and modern approaches in fine arts education to enhance students’ creativity, aesthetic perception, and visual thinking. It analyzes the use of project-based learning, interactive lessons, digital technologies, and national art examples to foster innovative and critical thinking in students. The study emphasizes the importance of student-centered pedagogy and a creative learning environment for developing original artistic expression.